Evaluation Of The Use Of Artificial Intelligence For Optimizing Internship Reports At SMK Karmel - Novianti Hutasoit; Sophia Tri Setyawati; Wasitohadi (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2024)
This study aims to explore the application of Artificial Intelligence (AI) technology in the preparation of internship reports at SMK Karmel and analyze its impact on efficiency, quality, and the development of students' skills. In this research, AI is used to assist students in composing reports by providing structural guidance, content analysis, and suggestions for improving writing quality. The findings of the study indicate that the use of AI technology enhances the efficiency of report preparation by reducing the time needed for writing and revising reports. Additionally, the quality of internship reports has significantly improved in terms of structure, grammar, and writing fluency. However, several challenges remain in its implementation, such as the readiness of students and teachers to use this technology and AI’s limitations in understanding the context of students' specific experiences. The study also found that the implementation of AI not only improves students' technical skills in using technology but also enriches their critical and analytical thinking skills. Based on these findings, it is recommended to provide further training for students and teachers and to continue developing the AI platform to enhance its ability to adapt to students' contextual experiences